Analisis Pergerakan Wacana Dugaan Pelecehan Seksual pada Beberapa Finalis Miss Universe Indonesia - Kristianti, Yuliana; Mashud, Mashud; Sari, Nita Puspita (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
Allegations of sexual harassment against several Miss Universe Indonesia finalists have drawn pros and cons. Online mass media in Indonesia shows that there are parties who support the victim, but there are also those who doubt the victim's statement because it has not been proven by law. This research aims to observe and analyze the movement of discourse as seen from various statements from parties supporting victims, such as the Minister of Women's Empowerment and the Fourth Winner of Miss Universe Indonesia, as well as parties who doubt allegations of sexual harassment, such as former CEO of Miss Universe Indonesia Poppy Capella. Data collection was carried out using documentation methods and recording techniques which were then analyzed using Sawirman's BREAK (Base, Relationship, Equilibrium, Actualization, and Keberlanjutan wacana/Discourse Sustainability) critical discourse analysis theory. The results of this research show that the discourse movement regarding alleged sexual harassment among the Miss Universe Indonesia finalists is divergent-divergent (DIDI). Abstrak Dugaan pelecehan seksual terhadap beberapa finalis Miss Universe Indonesia menuai pro dan kontra. Media massa online di Indonesia menunjukkan ada pihak yang mendukung korban, namun ada juga yang meragukan pernyataan korban karena belum dibuktikan kebenarannya oleh hukum. Penelitian ini bertujuan untuk mengamati dan menganalisis pergerakan wacana yang dilihat dari berbagai pernyataan pihak-pihak pendukung korban, seperti Menteri Pemberdayaan Perempuan dan Pemenang Keempat Miss Universe Indonesia, serta pihak yang meragukan dugaan pelecehan seksual, seperti Mantan CEO Miss Universe Indonesia Poppy Capella. Pengumpulan data dilakukan dengan metode dokumentasi dan teknik pencatatan yang selanjutnya dianalisis menggunakan teori analisis wacana kritis BREAK (Basis, Relasi, Ekulibrium, Aktualisasi, dan Keberlanjutan wacana) dari Sawirman. Hasil penelitian ini menunjukkan bahwa gerakan wacana dugaan pelecehan seksual pada para finalis Miss Universe Indonesia bersifat divergen-divergen (DIDI).